Export diversification and economic growth an analysis of Colombia's export competitiveness in the European Union's market - Mejia, Juan Felipe (Physica-Verlag, 2011)
The main research problem addressed in the book is the one regarding the role that export diversification could play for enhancing economic growth in Colombia, both in terms of new products and new geographic markets. The underlying motivation for centering the analysis on the European Union?s market are manifold, reaching from the evident concentration of exports , both in terms of composition and markets that Colombia still shows, to the small amount of empirical studies analyzing the current status and potentialities of the commercial relations between Colombia and the European Union.